Applying the framework for developing and evaluating complex interventions to increase family communication about hereditary cancer - Deborah L. Cragun; Paige Phillips Hunt; Marleah Dean; Anne Weidner; Andrea K. Shields; Ann Tezak; Tuya Pal (Elsevier, 2023)
Objective: Evaluate an intervention to increase family communication (FC) of positive hereditary cancer test results using the Framework for Developing and Evaluating Complex Interventions (FDECI). Methods: We developed 'programme theory' during the FDECI development phase by aligning intervention components with behavior change techniques (BCTs) and theoretical factors expected to improve FC. During the feasibility phase, we obtained feedback from 12 stakeholder interviews. Results: Intervention components aligned with a total of 14 unique BCTs for which prior evidence links the BCT to theoretical factors that influence behavior change. Constructive stakeholder feedback included: more information desired, rewording to support autonomy by highlighting options, and improvements to navigation, visuals, and audio. Positive comments included: comprehensiveness of materials, modeling of conversations, and usefulness of the materials for helping a person prepare to share positive test results. Conclusion: The first FDECI phases were helpful for improving the intervention and planning our ongoing effectiveness and future implementation phases. Innovation: Our application of the FDECI is novel, including plans to test our 'programme theory' using coincidence analysis (CNA) to determine who accesses which intervention materials, how utilizing certain materials impact the aligned theoretical factors, and whether these in turn make a difference in the behavioral outcome.